HYBRID TONGUES: CODE-SWITCHING AND LEXICAL BORROWING UZBEK ENGLISH RUSSIAN MULTILINGUAL LANGUAGES - Adiba Kasimova; Abduvaliyeva Ma’mura (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines the phenomenon of hybrid language use in Uzbekistan, focusing on code-switching and lexical borrowing in Uzbek–English– Russian multilingual contexts. Drawing on concepts from Sociolinguistics, the study analyzes structural patterns, communicative functions, and sociocultural motivations of multilingual speech. It demonstrates that code-switching and borrowing are systematic and meaningful processes that reflect speakers’ linguistic competence and adaptability. The findings suggest that hybrid language practices are not signs of linguistic decline but rather indicators of dynamic language evolution in response to globalization, technological development, and cultural interaction.